iVS analysis to evaluate the impact of scaffold diversity in the binding to cellular targets relevant in cancer - Agostino Cilibrizzi; Giuseppe Floresta; Vincenzo Abbate; Maria Paola Giovannoni (Taylor & Francis Group, 2019)
This study reports the application of inverse virtual screening (iVS) methodologies to identify cellular proteins as suitable targets for a library of heterocyclic small-molecules, with potential pharmacological implications. Standard synthetic procedures allow facile generation of these ligands showing a high degree of core scaffold diversity. Specifically, we have computationally investigated the binding efficacy of the new series for target proteins which are involved in cancer pathogenesis. As a result, nine macromolecules demonstrated efficient binding interactions for the molecular dataset, in comparison to the co-crystallised ligand for each target. Moreover, the iVS analysis led us to confirm that 27 analogues have high affinity for one or more examined cellular proteins. The additional evaluation of ADME and drug score for selected hits also highlights their capability as drug candidates, demonstrating valuable leads for further structure optimisation and biological studies.